Desain Prototip Kontrol pH Nira Tebu dengan Konsep Overflow Menggunakan PLC - Akhmad, Akhmad Fahruzi; Andy Dwi Cahyo; Wahyu Setyo Pambudi (Jurnal Elektronika dan Otomasi Industri, 2025)
In the process of processing sugarcane juice into granulated sugar in the sugar industry, refining sugarcane juice is a factor that affects the quality of sugarcane. The method used to refine sugarcane juice is called defakasi, which is mixing it with lime milk. The aim is to increase the pH of sugarcane juice. From this problem, a pH control of sugarcane juice is proposed with the overflow concept using the PID algorithm. For the controller using the outseal nano V5 type PLC and the pH sensor is sen0161. PID control is used to regulate the flow rate of lime milk that enters the mixing tank through the pump. The results showed that the pH sensor had a relative error of less than 5% with a fluctuation of 4.73%. The selected gain parameters were KP = 0.8; KI = 0.5 and KD = 0.2 so that the time required to increase the pH value of sugarcane juice which was initially around 4.5 - 5 to 7 took about 60 seconds. While the overshoot value reached 19.86% and the steady state error was 6.71%. And the results of the pH of sugarcane juice after being controlled showed a relative error of 12.28%.